Carpal tunnel syndrome caused by tophi deposited under the epineurium of the median nerve: A case report - Zhang, Wenzhong; Feng, Qingbo; Gu, Jiaxiang; Liu, Hongjun (Frontiers in Surgery, 2023)
Introduction Usually caused by compression of the wrist's median nerve, carpal tunnel syndrome (CTS) is one of the most common types of peripheral neuropathy. Tophi deposited under the epineurium of the median nerve compress the median nerve, leading to CTS, which is very rare. Case presentation We report a 64-year-old man with a history of tophaceous gout who presented with typical CTS symptoms and was admitted to our hospital. A physical examination revealed swelling over the right volar aspect of the carpal region, and he was unable to flex due to subcutaneous rigidity. Tinel's sign and Phalen's maneuver were positive. Electrophysiological studies confirmed the diagnosis of CTS. A carpal tunnel release and surgery to remove the gouty tophus of the right wrist were performed when serum uric acid levels were within normal limits (5.8 mg/dl). During the operation, tophi deposited under the epineurium of the median nerve were found, and the tophi were completely removed. Operative findings confirmed the diagnosis of CTS due to gout. The patient recovered uneventfully without signs of recurrence of gout and CTS symptoms during a 1-year follow-up period. Conclusion A gouty tophus is an uncommon cause of CTS, and CTS may be caused by gouty tophi if there is evidence of extrinsic compression of the median nerve or symptoms emanating from the carpal tunnel.